Cellular pathogenesis of Duchenne muscular dystrophy: progressive myofibre degeneration, chronic inflammation, reactive myofibrosis and satellite cell dysfunction - Paul Dowling; Dieter Swandulla; Kay Ohlendieck (PAGEPress Publications, 2023)
Duchenne muscular dystrophy is a highly progressive muscle wasting disease of early childhood and characterized by complex pathophysiological and histopathological changes in the voluntary contractile system, including myonecrosis, chronic inflammation, fat substitution and reactive myofibrosis. The continued loss of functional myofibres and replacement with non-contractile cells, as well as extensive tissue scarring and decline in tissue elasticity, leads to severe skeletal muscle weakness. In addition, dystrophic muscles exhibit a greatly diminished regenerative capacity to counteract the ongoing process of fibre degeneration. In normal muscle tissues, an abundant stem cell pool consisting of satellite cells that are localized between the sarcolemma and basal lamina, provides a rich source for the production of activated myogenic progenitor cells that are involved in efficient myofibre repair and tissue regeneration. Interestingly, the self-renewal of satellite cells for maintaining an essential pool of stem cells in matured skeletal muscles is increased in dystrophin-deficient fibres. However, satellite cell hyperplasia does not result in efficient recovery of dystrophic muscles due to impaired asymmetric cell divisions. The lack of expression of the full-length dystrophin isoform Dp427-M, which is due to primary defects in the DMD gene,  appears to affect key regulators of satellite cell polarity causing a reduced differentiation of myogenic progenitors, which are essential for myofibre regeneration. This review outlines the complexity of dystrophinopathy and describes the importance of the pathophysiological role of satellite cell dysfunction. A brief discussion of the bioanalytical usefulness of single cell proteomics for future studies of satellite cell biology is provided.